Mali : Poverty Reduction Strategy Paper-Progress Report. (IMF Staff Country Reports; Country Report ;, 2010)
Following an evaluation of the first Poverty Reduction Strategy Framework (PRSF) of Mali, the government adopted the Growth and Poverty Reduction Strategy Framework (GPRSF) document, which aims at reducing poverty and achieving the MDGs. The Accelerated Growth Strategy, which maintains macroeconomic stability and pursues structural reforms, is based on improvement of governance and renewal of public action, development of productive and private sectors, and investment in human resources. The GPRSF groups provide details regarding implementation of sector policies and strategies, budget implementation status, and recommendations. It is recommended to ensure monitoring-evaluation of poverty reduction activities through the GPRSF action plan.